KARAKTERISTIK BATUAN DAN HUBUNGANNYA DENGAN KUANTITAS & KUALITAS AIR TANAH DI DAERAH CIPUNAGARA DAN SEKITARNYA - -, Aton Patonah; -, Sapari Dwi Hadian (Bulletin of Scientific Contribution, 2013)
Administratively, Cipunagara area is part of Subang Regency, West Java province. Geographically, the research area are located between 107o30’00” – 107o52’30” E and 06o37’30” – 06o52’30” S. Purposes of this research are to know the characterization of water quantity and quality based on petrology and geochemistry methods. The results of this research show that quantities of water depend on porosity. Secondary porosity advanced on basalt and andesite igneous rocks because of deformation. Those conditions give the rocks the ability to reserve much water. Meanwhile primary porosity advanced on tuff and breccia rocks. Based on water geochemistry analysis, the relationship between mineral in igneous rocks (andesite and basalt) that contain cation Ca and water quality can be found. Water in research area contains high cation Ca that good for water drinking